ANALISIS MOTIVASI BELAJAR SISWA SMP KELAS VIII BERBANTUAN POWER POINT INTERAKTIF PADA MATERI BANGUN RUANG SISI DATAR - Ghina Yuliana Sa'diah; Rippi Maya; Luvy Sylviana Zanthy; Ratni Purwasih (IKIP Siliwangi, 2022)
This study aims to dissect students' learning inspiration on the material for building flat sides with the help of interactive Powerpoint. The method used in this exam is a qualitative descriptive technique. The subjects of this study were 6th grade students of SMP Negeri 1 Ciwidey, consisting of 2 male students and 4 female students. The information retrieval technique uses a student learning motivation scale on the flat-sided building material assisted by interactive Powerpoint media which contains 10 statements with 5 positive statements and 5 negative statements. The results of data analysis in this study indicate that students are included in the very good category, which is 82.1% of the results of calculations using Microsoft Excel. Utilization of interactive Powerpoint media can help students in learning the material for building flat sides.